Wednesday

April 23, 2014

April 23, 2014

Posted by **Jessica** on Tuesday, July 21, 2009 at 10:45pm.

3m^2 -75

This is how I started to work it out.

(3m-23)(m-5)

- algebra -
**MathMate**, Tuesday, July 21, 2009 at 10:57pmStart by factoring out the GCF, which in this case is 3.

So you get

3m²-75

=3(m²-25)

The part in parentheses is the difference of two squares. Look up your course notes to see how to factor this part, namely using the standard form:

(A²-B²) = (A+B)(A-B)

**Related Questions**

factoring - let f(m)=m^3 + 3m^2 + 3m + 1 notice f(-1) = 0, so m+1 is a factor. ...

algebra - 1. Evaluate the polynomial for x=3 and x=-3: the value of -6x +8 is - ...

algebra - Posted this question and part of the answer was incorrect. a) 4L/3 = 6...

Algebra - 3m^3 + 27m = 3m(m^2 + 9) = 3m(m + 3)(m – 3) I miss something? is this ...

Algebra - 3m^3 + 27m = 3m(m^2 + 9) = 3m(m + 3)(m – 3) its is not done? is this a...

mat117/algebra - factor each polynomial completely. to begin, state which method...

Man My Algebra must be annoying - 3m __ for m =20 and m = 1 5 __ 3 A. 3m = 320...

Algebra - 3m^3 + 27m = 3m(m^2 + 9) = 3m(m + 3)(m – 3)

Math - -75= 5(3m-3)-3m. Can someone explained this problem to me and how to ...

math - Factor the four-term polynomial. mn - 15 + 3m - 5n